Information and Congressional Hearings - Daniel Diermeier; Timothy J. Feddersen (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
While Congressional scholars agree that hearings are an important activity there is little consensus on their role in the legislative process. The traditional literature on hearings pplays down their role as mechanisms of disseminating information because committee members often do not appear persuaded by the information they reveal. In this paper we explore the premise that hearings may not be informative to committees but may provide crucial information to the floor. We show that, if hearings have some intrinsic informative content and are costly, even extreme committees can transmit useful information to the floor. Furthermore, the possibility of holding hearings creates an incentive for extreme committees to specialize and reveal information simply by the decision whether to hold hearings.
Keywords: 330